Efficacy of the Nutritional Supplement, EvenFlo, in the Management of Sickle Cell Disease: A Randomized Controlled Trial - Richard Muga; Arthur Ajwang; James Ouma; Josephine Ojigo; Juliana Otieno; Peter Okoth; Caroline Wafula; Sophia Ajwang; David Ogolla; Abraham Hollist; James Adefisoye (Library & Knowledge Services and Nursing & Health Sciences Research Departments, 2020)
Background: In this study, we investigated if a combination of the nutraceutical supplement, EvenFlo and folic acid will be superior to the standard stand-alone use of folic acid. Methods: We conducted a randomized double-blind, active-controlled, clinical trial. A total of 70 subjects with SCD ages 5-12 years were enrolled into the study with 35 in the intervention group and 35 in the control group; 61 completed the trial (32 from the intervention group and 29 from the control group). Results: Participants in the intervention group were significantly less likely to experience crises compared to subjects in the control group. None of the subjects in the intervention group experienced any form of vasoocclusive crisis (VOC) compared to 93.1% of the subjects in the controlled group. Additionally, the intervention group experienced a significantly higher increase in their hemoglobin concentration from baseline (2.92 g/dL, 95% CI [2.33, 3.51]) compared the control group (1.77 g/dL, 95% CI [1.00, 2.54]). The intervention group experienced a significantly higher increase in their mean weight from baseline (4.47 Kg, 95% CI [4.02, 4.92]) while the control group experienced a decrease (-1.05 Kg, 95% CI [-1.60, -0.51]). Conclusions: EvenFlo is a nutritional supplement effective in the management of SCD when combined with folic acid; its beneficial effect would be useful in boosting the hemoglobin concentration and weight indices individuals with SCD as well as and in limiting the crises they suffered.